Impacts of microfinance institution in improving SMEs in Zanzibar. Case study of BRAC micro finance (Singaporean Journal of Business Economics and Management, 2026)
The study aimed to explore the impact of microfinance institution (MFI) services on the improvement of Small and Medium Enterprises (SMEs) in Zanzibar, with a specific focus on BRAC Microfinance. SMEs play a critical role in driving employment creation, poverty reduction, and local economic development in Zanzibar; however, many continue to face challenges in accessing formal financial services. The research employed a descriptive quantitative design, utilizing structured questionnaires administered to 240 SME owners in the Urban District of Zanzibar. Data were analyzed using descriptive statistics and presented through frequency tables and figures to capture respondents’ perceptions of microfinance accessibility, training, and loan conditions. The findings revealed that BRAC’s microfinance services are generally accessible, with a majority of respondents agreeing that institutions are located within reasonable distances and that information about services is readily available. Training programs were found to significantly enhance SME owners’ financial management, business planning, and marketing capabilities, leading to improved operational efficiency. Despite these positive outcomes, challenges related to high interest rates, short repayment periods, and collateral requirements continue to constrain SME growth and sustainability. The study concludes that BRAC’s interventions have positively influenced SME development in Zanzibar by combining financial access with entrepreneurial training. It recommends that microfinance institutions and policymakers strengthen client-centered financial products, simplify loan processes, and continue investing in capacity-building programs to enhance the long-term viability of SMEs.